Development and validation of an instrument to measure quality management practices - Soria García, José; Martínez Lorente, Ángel Rafael (Avances en Supervisión Educativa, 2010)
The main objective of this research is to identify and confirm the most important dimensions in the quality management that can be applied in the secondary schools, with the purpose of developing a measure instrument that can be used, with enough reliability and validity, for these educational institutions. This could help to know the school reality, pointing out the strong points and the areas of improvement. Our analysis emphasizes quality management practices (inputs) rather than quality performance (outputs). Starting from this diagnosis, proposals of improvement in coherence with the detected necessities could be elaborated, and a dynamic of continuous and sustainable improvement could be introduced. In the study that we present here, a panel of experts was constituted to carry out a type Delphi investigation with the intention of using their knowledge to discriminate among the different indicators of the scale, and to specify which of them should be part of the measure instrument.
Keywords: quality management practices; dimensions; institutions educational; indicators; continuous improvement; Delphi